Tatalaksana Malaria Berat - Gigaramadan Sema; Hanna Mutiara; Tri Umiana Soleha (Medula, 2023)
Malaria is a disease caused by the infection of Plasmodium parasite. Severe Malaria is accompanied by complications such as cerebral Malaria, seizures, acute kidney failure, hemodynamic shock, and so on. intravenous artesunate is the first-line treatment for severe Malaria caused by all Plasmodium species. Early RRT therapy is necessary to manage acute renal failure, also careful fluid resuscitation is important to prevent lethal pulmonary edema. Delayed-onset hemolysis following Artesunate administration necessitate hemoglobin checks and post-treatment monitoring. ACT treatment is the first line treatment after complications have subsided, followed by primaquine administration to treat relapse cases. G6PD testing is required before primaquine administration to prevent hemolysis.